A Longitudinal Analysis of Traffic-Violation Behaviours among Two Groups of Motorcyclist in Bandung, Indonesia - Joewono, T.B.; Legi, S.D.; Tarigan, A.K.M. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The capability and limitations of car drivers or motorcyclists are believed to change over time as a response to external and internal triggers. As a fact, studies regarding behaviour of young motorcyclists from developing countries are very rare while motorcyclists from developed and developing are believed as different. This study aims to explore the change of behavior of young motorcyclists in committing traffic violations in urban areas from experience in developing countries. Analyses employed datasets collected using questionnaire survey from Bandung, Indonesia from two periods, namely 2010 and 2017. Comparison analyses were completed to compare traffic violations attributes between the two datasets. Two causal models from two data collections were estimated using structural equation modelling to analyse the influencing factors to traffic violations as well as to analyse the relationships of influencing factors, characteristics of motorcyclist, and type of violations. Between the two datasets it is found the difference of the type of violations which implies the change of attitudes in committing traffic violations, while the change of causal relationships is not found in the models. This study confirms the flexibility of behavior change in riding motorcycles between young motorcyclists, while relationships among constructs seem more stable.